2004
DOI: 10.1177/009286150403800303
|View full text |Cite
|
Sign up to set email alerts
|

From Informed Consent through Database Lock: An Interactive Clinical Trial Conducted Using the Internet

Abstract: This paper describes an interactive clinical trial that utilized the World Wide Web and Internet technologies throughout the conduct of the trial from informed consent through database lock and study closure. We believe this is the first development and administration of an interactive clinical trial that utilized the Internet for trial execution while complying with regulations for clinical trials conducted under an Investigational New Drug application.A United States study of tadalafil, a phosphodiesterase-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
18
0
2
Order By: Relevance
“…Other clinical studies that have used remote approaches to evaluate therapeutics have demonstrated the feasibility of such an approach. [38][39][40][41][42][43] That said, contacting many individuals was difficult because of telephone blocking services, absence of a prior relationship, and incomplete information provided. The inclusion of data checks to identify any missing responses would likely have reduced inadvertent omissions in sometimes lengthy forms and surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies that have used remote approaches to evaluate therapeutics have demonstrated the feasibility of such an approach. [38][39][40][41][42][43] That said, contacting many individuals was difficult because of telephone blocking services, absence of a prior relationship, and incomplete information provided. The inclusion of data checks to identify any missing responses would likely have reduced inadvertent omissions in sometimes lengthy forms and surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Large pharmaceutical firms, notably Eli Lilly and Company 69 and Pfizer Inc, 72 have invested in developing web-based approaches that include greater participant engagement and remote assessments. The FDA is also willing to support such novel approaches.…”
Section: Future Directionsmentioning
confidence: 99%
“…Signed consent forms must be sent to sites via mail or email, creating unnecessary delays. This has been the case with other primarily internet-based clinical trials [ 106 ]. With the continuing integration of internet-based communications into all aspects of medicine and research, methods of obtaining electronic signatures securely should increasingly become part of standard research practice, as they have been implemented successfully in other primarily internet-based clinical trials [ 107 109 ].…”
Section: Discussionmentioning
confidence: 76%